2020
DOI: 10.3389/fphys.2020.00922
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine-Mediated Attenuation of Mechanoelectric Feedback in Atrial Myocyte Monolayers

Abstract: Background: Mechanical stretch increases Na + inflow into myocytes, related to mechanisms including stretch-activated channels or Na + /H + exchanger activation, involving Ca 2+ increase that leads to changes in electrophysiological properties favoring arrhythmia induction. Ranolazine is an antianginal drug with confirmed beneficial effects against cardiac arrhythmias associated with the augmentation of I NaL current and Ca 2+ overload. Objective: This study investigates the effects of mechanical stretch on ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Despite propensity score matching was performed, optimal statistical matching was challenging, and this may influence the outcome, thus results should be taken with caution. The potential benefits of mechanical stretch pharmacologic modifiers were not evaluated 20 . Moreover, the exclusion of patients with non‐inducible AF or severe LA scarring will reduce the potential effects of ablation in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite propensity score matching was performed, optimal statistical matching was challenging, and this may influence the outcome, thus results should be taken with caution. The potential benefits of mechanical stretch pharmacologic modifiers were not evaluated 20 . Moreover, the exclusion of patients with non‐inducible AF or severe LA scarring will reduce the potential effects of ablation in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of mechanical stretch pharmacologic modifiers were not evaluated. 20 Moreover, the exclusion of patients with non-inducible AF or severe LA scarring will reduce the potential effects of ablation in this population.…”
Section: Limitationsmentioning
confidence: 99%
“…Recently, Cho et al [471] demonstrated the antiarrhythmic effects of CDCs in rats with This study used HL-1 CM monolayers as models of arrhythmic substrate. Despite being an in vitro cell line capable of presenting a mature cardiac phenotype and being widely used to study cardiac electrophysiology and arrhythmias [477][478][479][480][481][482][483][484][485][486], their use has several limitations that must be taken into account. HL-1 cells, although being mature, are of murine origin and present important electrophysiological differences with adult human cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological properties of cell cultures were analyzed by processing CaT recordings as illustrated in Figure 7.1b. with custom software written in MATLAB, quantifying dominant frequency (DF), complexity, curvature, rotor meandering and CV as described by Climent et al [477,478].…”
Section: Calcium Image Processingmentioning
confidence: 99%
“…Custom software written in MATLAB was used to perform optical mapping image processing and analysis [30]. Data was filtered to remove fluorescence noise, applying a spatial Gaussian filter (kernel size = 5) and a temporal smoothing filter (kernel size = 5) as described in previous studies [31]. Finally, CaT signals of each pixel were normalized between 0 and 1 [32].…”
Section: Optical Data Processing and Analysismentioning
confidence: 99%